2019
DOI: 10.7748/cnp.2018.e1506
|View full text |Cite
|
Sign up to set email alerts
|

Is patient information on palliative care good enough? A literature review and audit

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Participants also felt educational resources about specialist palliative care were lacking for patients considering phase I trial enrolment. An audit of palliative care information resources available to cancer patients in 20 hospitals revealed that information leaflets are often not in routine circulation and are often only distributed to patients after a palliative care referral 32. Specialist palliative care information should be made more readily available in outpatient and inpatient settings to raise awareness of the role of palliative care and to address misconceptions.…”
Section: Discussionmentioning
confidence: 99%
“…Participants also felt educational resources about specialist palliative care were lacking for patients considering phase I trial enrolment. An audit of palliative care information resources available to cancer patients in 20 hospitals revealed that information leaflets are often not in routine circulation and are often only distributed to patients after a palliative care referral 32. Specialist palliative care information should be made more readily available in outpatient and inpatient settings to raise awareness of the role of palliative care and to address misconceptions.…”
Section: Discussionmentioning
confidence: 99%
“…Timely introduction of palliative care is an important facilitating factor to successful referrals (Fliedner et al, 2019; McCaughan et al, 2018; Taylor et al, 2018); however, our study showed the timing of these conversations remains difficult for patients and HCPs. Dedicating time to discussing a patient's current perception of their health, treatment and prognosis has been shown as a key underlying factor in successful palliative care trials (Bakitas et al, 2017) and can enhance understanding of palliative services and the relevance to future care (Fliedner et al, 2019).…”
Section: Discussionmentioning
confidence: 66%
“…Timely introduction of palliative care is an important facilitating factor to successful referrals (Fliedner et al, 2019;McCaughan et al, 2018;Taylor et al, 2018); however, our study showed the timing of these conversations remains difficult for patients and HCPs.…”
Section: Discussionmentioning
confidence: 80%
“…Similarly,Taylor et al, found that less than 13% of inpatient units, 7% of outpatient units and 25% of daily chemotherapy units have written materials available on palliative care. To increase patients' awareness of palliative care services and eliminate misconceptions related to palliative care, it is imperative to prepare appropriate educational lea ets and make them available to patients in oncology departments to increase patient information and help start a discussion about the role of palliative care and its' integration into the plan of care in a timely manner (26).…”
Section: Discussionmentioning
confidence: 99%
“…Some patients think that any patient who is referred to palliative care has reached the end of his / her lifespan (24). Lack of palliative care education programs for patients and their families is a barrier that reduces use of palliative care (25).In fact, lack of information is an important challenge at present and should be investigated because cancer patients need to be aware of the goals and bene ts of palliative care and have access to this information in various departments of oncology (26). It is very important to identify patients' awareness in this regard and to consider patients' decisions about type of care will use for the remainder of their lives (27).…”
Section: Introductionmentioning
confidence: 99%